2021
DOI: 10.1016/j.annonc.2021.08.2133
|View full text |Cite
|
Sign up to set email alerts
|

LBA53 Sintilimab plus chemotherapy (chemo) versus chemo as first-line treatment for advanced gastric or gastroesophageal junction (G/GEJ) adenocarcinoma (ORIENT-16): First results of a randomized, double-blind, phase III study

Abstract: Sintilimab plus chemotherapy (chemo) versus chemo as first-line treatment for advanced gastric or gastroesophageal junction (G/GEJ) adenocarcinoma (ORIENT-16): First results of a randomized, double-blind, phase III study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 0 publications
0
77
1
3
Order By: Relevance
“…As presented at ESMO 2021, the first results show a survival benefit of the combination therapy in all randomized patients versus chemotherapy plus placebo (median OS 15.2 vs. 12.3 mths, HR 0.77 (95% CI 0.63-0.94), p = 0.0090). This effect was even more clear in the group of patients with PD-L1 CPS ≥ 5 tumors (median OS 18.4 vs. 12.9 mths (HR 0.66 (95% CI 0.51-0.86), p = 0.0023)) [23].…”
Section: Palliative First-line Therapymentioning
confidence: 89%
“…As presented at ESMO 2021, the first results show a survival benefit of the combination therapy in all randomized patients versus chemotherapy plus placebo (median OS 15.2 vs. 12.3 mths, HR 0.77 (95% CI 0.63-0.94), p = 0.0090). This effect was even more clear in the group of patients with PD-L1 CPS ≥ 5 tumors (median OS 18.4 vs. 12.9 mths (HR 0.66 (95% CI 0.51-0.86), p = 0.0023)) [23].…”
Section: Palliative First-line Therapymentioning
confidence: 89%
“…Data from the phase 3 CheckMate-649 trial ( 22 ) showed that the first-line combination therapy of nivolumab and chemotherapy showed a survival benefit in patients with advanced gastric cancer, in contrast to the chemotherapy alone. ORIENT-16 ( 23 ) demonstrated sintilimab in combination with chemotherapy significantly prolonged OS (18.4 months) in the first-line treatment of advanced gastric cancer, superior to that of nivolumab. In addition to its low price, sintilimab also had significantly lower toxicities than pembrolizumab and nivolumab.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with CPS ≥ 10 tumors, the median OS was 20.0 months versus 11.3 months, in favor of the sintilimab arm. Although these results are encouraging, the data regarding patients with lower CPS levels was not explicitly reported, yet the results do show the same phenomenon as seen with CHECKMATE-649, with less pronounced HRs as patients with lower PD-L1 levels were added to the analyses [ 45 ]. These results are consistent with prior studies and support the use of sintilimab in patients with CPS ≥ 10 tumors.…”
Section: The Use Of Ici In the First-line Settingmentioning
confidence: 96%
“…ORIENT-16 was a randomized, double-blind, phase 3 trial that evaluated the efficacy and safety of sintilimab plus CAPOX vs. placebo plus CAPOX for first-line treatment of advanced gastric and GEJ AC among Chinese patients [ 45 ]. In the prespecified interim analysis, 650 patients were randomized to receive sintilimab plus CAPOX ( n = 327) and placebo plus CAPOX ( n = 323).…”
Section: The Use Of Ici In the First-line Settingmentioning
confidence: 99%